Freedom or Destruction? Gejza Vámoš’ The Atoms of God in the Context of Maladic Discourse - Goszczyńska, Joanna (Porównania, 2024)
The author of the article interprets the novel of the Slovak writer of the interwar period by focusing on several of its aspects: the pathographic dimension, the sphere of corporeality in the experience of illness, the defective personality of the main character (the doctor) and the metaphorization of illness. The philosophical background of Vámoš’s attitude, the philosophy of Nietzsche and Schopenhauer, was also considered. For the author of the article, however, the thought of Cioran was particularly inspiring.